2015
DOI: 10.1007/978-3-319-15925-6
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Mediated Agency in Educational Reform in China

Abstract: More information about this series at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 71 publications
0
14
0
6
Order By: Relevance
“…Li et al, 2016;Zhang and Pang, 2016). Moreover, China's particular combination of system size and socio-cultural norms create a unique context for enacting leadership aimed at fostering TPL (Tang et al, 2014;Walker and Qian, 2015;Yang, 2015;Yin et al, 2014). Thus, the research has potential to make contributions to leadership research and practice both in China and globally.…”
mentioning
confidence: 99%
“…Li et al, 2016;Zhang and Pang, 2016). Moreover, China's particular combination of system size and socio-cultural norms create a unique context for enacting leadership aimed at fostering TPL (Tang et al, 2014;Walker and Qian, 2015;Yang, 2015;Yin et al, 2014). Thus, the research has potential to make contributions to leadership research and practice both in China and globally.…”
mentioning
confidence: 99%
“…This study shows how CLIL teacher agency changes dynamically reflecting the teachers' experienced challenges. It also suggests the sociocultural understanding of teacher agency, in the sense that it is not a straightforward issue that can be understood merely as a personality trait of an individual teacher or as a predictable reaction to existing contextual factors (Yang, 2015). Accordingly, both individual and contextual aspects are entwined in the complex experiences of agency of CLIL teachers.…”
Section: Discussionmentioning
confidence: 99%
“…Rapidly changing educational contexts set continuous demands on teachers who are the actual implementers of educational policies in the classroom. For these reasons, teachers' roles and agency have become central issues in education and educational research (Yang, 2015). It is therefore crucial that research actively seeks to understand CLIL teachers' voices to better understand the challenges of their work (Moate, 2011b).…”
mentioning
confidence: 99%
“…Similarly, Berry (2006) found that teachers adapted their writing instruction in ways that connected with their implicit theories about teaching, learning, and disability. While the relationship between beliefs and actions is deemed as cause-effect, Yang (2015) suggests that this relationship may be reciprocal. In other words, beliefs and practices inform each other.…”
Section: Teacher Beliefs Knowledge and Challenges Related To Writing ...mentioning
confidence: 99%